Accumulation of Heavy Metals and Metalloid in Foodstuffs from Agricultural Soils around Tarkwa Area in Ghana, and Associated Human Health Risks - Bortey-Sam, N.; Nakayama, S.M.M.; Akoto, O.; Ikenaka, Y.; Fobil, J.N.; Baidoo, E.; Mizukawa, H.; Ishizuka, M. (International Journal of Environmental Research and Public Health, 2015)
This study was carried out to assess the extent of heavy metals and metalloid accumulation from agricultural soils to foodstuffs (viz, M. esculenta (cassava) and Musa paradisiaca (plantain)) around thirteen neighboring communities within Tarkwa, Ghana; and to estimate the human health risk associated with consumption of these foodstuffs. Concentrations of As, Cd, Co, Cr, Cu, Ni, Pb, and Zn were measured with an inductively coupled plasma-mass spectrometer and mercury analysis was done using a mercury analyzer. From the results, 30% of cassava samples collected, contained higher concentrations of Pb when compared to Codex Alimentarius Commission standard values. Bioconcentration factor indicated that Ni had higher capacity of absorption into food crops from soil than the other heavy metals. For both children and adults, the target hazard quotient (THQ) of Pb in cassava in communities such as Techiman, Wangarakrom, Samahu, and Tebe (only children) were greater than 1, which is defined as an acceptable risk value. This indicated that residents could be exposed to significant health risks associated with cassava consumption.
Keywords: metals; metalloid; health risk; foodstuff; bioconcentration factor; target hazard quotient